Analisis Struktural dan Nilai Pendidikan Karakter pada Novel Si Anak Savana karya Tere Liye serta Pemanfaatannya Sebagai Bahan Ajar di SMA - Ernawati, Siti; Al Gadri, Henri Henriyan (Universitas Mathla'ul Anwar Banten, 2023)
This research aims to describe the structure of the novel Si Anak Savana by Tere Liye and the value of character education and its use as teaching material in schools. The research method used is descriptive qualitative by describing the results of the analysis in the form of the structure and value of character education in the novel Si Anak Savana by Tere Liye which is then used as learning material for Indonesian Language and Literature in Schools. The novel Si Savana Child by Tere Liye has a novel structure that focuses on theme, characters and characterization, setting, plot, language style, point of view and message and there are character education values, namely religious, honest, tolerant, disciplined, hard work, creative, independence, curiosity, love of the country, respect for achievements, friendship (communicative), love of peace, environmental care, social care, and responsibility